A dança na inclusão de pessoas com deficiência intelectual - Alcaras, Giovana Marsola [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The prejudices generated by the deficiencies and limitations they impose on the individual, allied to the demands of society that values the beautiful, the perfect and the intellectual, demand from the family, the school and the community reactive patterns that are unfavorable to people with disabilities or conduct problems. Therefore, the lyrical image of base, pillar, foundation, gives way to an epic image of struggle and a lot of effort to guarantee rights, as if please give people with disabilities their spaces of freedom. Society comfortably labels them and, by offering them scarce resources. So, in this context, we are interested in reflecting on dance as a powerful practice for the inclusion of people with intellectual disabilities to do so, we place the following hypothesis: dance as expressive practice has an exponential communicative potential that contributes to greater integration between the people who practice it, which would justify, therefore, the bet on this practice to promote greater inclusion of people with disabilities.

Os preconceitos gerados pelas deficiências e pelas limitações que impõem ao indivíduo, aliados às exigências da sociedade que valoriza o belo, o perfeito e a intelectualidade, exigem da família, da escola e da comunidade padrões reativos desfavoráveis às pessoas com deficiências ou problemas de conduta. Logo, a imagem lírica de base, pilar, fundamento, cede lugar a uma imagem épica de luta e de muito esforço para garantir direitos, como se fizéssemos favor de dar aos portadores de deficiências seus espaços de liberdade. Comodamente a sociedade os rotula e, ao oferecer-lhes escassos recursos. Assim, neste contexto, interessa-nos refletir sobre a dança como prática potente para a inclusão de pessoas com deficiência intelectual para tanto, situamos a seguinte hipótese: a dança como prática expressiva tem um exponencial potencial comunicativo que contribui para maior integração entre as pessoas que a praticam, o que justificaria, portanto, a aposta nesta prática para a promoção de uma maior inclusão de pessoas com deficiência.
Dance in the inclusion of people with intellectual disabilities
Keywords: Dance; Inclusion; People with intellectual disabilities; Social life; Dança; Integração social; Incapacidade intelectual; Inclusão; Pessoas com deficiência intelectual; Convívio social